2011
DOI: 10.20506/rst.30.3.2092
|View full text |Cite
|
Sign up to set email alerts
|

Organic livestock production: an emerging opportunity with new challenges for producers in tropical countries

Abstract: Agrochemicals, veterinary drugs, antibiotics and improved feeds can increase the food supply while minimising production costs in various livestock production systems around the world. However, these days, quality-conscious consumers are increasingly seeking environmentally safe, chemical-residuefree healthy foods, along with product traceability and a high standard of animal welfare, which organic production methods are said to ensure. Organic production is not only a challenge for producers in developing cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
9

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 5 publications
0
36
0
9
Order By: Relevance
“…To collect the necessary information from the respondents in both interviewing and observation was applied. The interview schedule contained the following informations; A) Checklist for organic goat production: Origin of livestock, Livestock feed, Livestock breeding, Health care, Living conditions, Record keeping (Chander et al, 2011). B) Socio-economic factors related to organic goat production: Gender, Age of the farmers, Education level, Household size, Occupation, Land size, Training, Source of capital, Number of goats, Description of the goat like breed, age, sex, weight, Purchase time, Goat rearing until marketing/ slaughter.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To collect the necessary information from the respondents in both interviewing and observation was applied. The interview schedule contained the following informations; A) Checklist for organic goat production: Origin of livestock, Livestock feed, Livestock breeding, Health care, Living conditions, Record keeping (Chander et al, 2011). B) Socio-economic factors related to organic goat production: Gender, Age of the farmers, Education level, Household size, Occupation, Land size, Training, Source of capital, Number of goats, Description of the goat like breed, age, sex, weight, Purchase time, Goat rearing until marketing/ slaughter.…”
Section: Methodsmentioning
confidence: 99%
“…The results of this study are similar to (Begum et al, 2007) where they reported that 83.3% farmers used vaccination, 80% farmers practiced deworming and 45% farmers removed sick animals from healthy animals. According to organic livestock production guidelines Chander et al, (2011) reported that 91%, 84% and 67% goats are considered to be organic on the basis of vaccination, antibiotic use and medication.…”
Section: Livestock Feeds and Foddermentioning
confidence: 99%
“…The research location was determined purposively in Plampang Sub-district on the consideration as one of the center producers of breeding cattle and beef cattle in the eastern region of Sumbawa Regency. The sample villages were chosen purposively, namely the villages of Plampang, Selante, and Muer on the basis of livestock density criteria, namely (1) low, (2) moderate, and (3) high (Chander et al, 2011) with the rural criteria were low, moderate, and high densities when the density of livestock were < 0.25, 0.25-1, and > 1 AU/ha of farm area range, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…A) Check list for organic buffalo production (Chander et al, 2011). Origin of livestock feeds and feeding, breeding, health care, living condition and record keeping of animals for farmers.…”
Section: Collection Of Datamentioning
confidence: 99%